The Impact of Financial Recession on the Efficiency of Invested Capital - Mohammed Jasim Mohammed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Financial management in the banking sector focuses on profitability, liquidity, and risk control to evaluate financial performance and capital utilization. Specific Background: Financial recession represents a condition that can influence how banks allocate and manage invested capital. Knowledge Gap: Prior studies rarely distinguish between different types of financial recession when examining capital efficiency in banking institutions. Aims: This study analyzes the relationship between financial recession and invested capital efficiency in commercial banks listed on the Iraq Stock Exchange. Results: Using panel data from 2012–2023 and statistical analysis with Eviews v13, the findings show that available financial recession is negatively related to return on invested capital and return on working capital, while potential financial recession shows a positive relationship with these indicators. Novelty: The study differentiates recession conditions into available and potential categories when assessing capital efficiency in banks. Implications: The findings provide insights for stakeholders in evaluating how recession conditions relate to the utilization of capital resources in the banking sector. Highlights:• Available Recession Conditions Correspond With Lower Profitability Ratios Derived From Capital Utilization.• Potential Recession Conditions Correspond With Higher Profitability Ratios Derived From Working Resources.• Empirical Evaluation Employs Panel Observations From Publicly Traded Banking Institutions During 2012–2023. Keywords: Financial Recession, Invested Capital, Capital Efficiency, Banking Sector, Iraq Stock Exchange.